Predictors of depression outcomes among abstinent methamphetamine‐dependent individuals exposed to an exercise intervention. (23rd April 2015) - Haglund, Margaret; Ang, Alfonso; Mooney, Larissa; Gonzales, Rachel; Chudzynski, Joy; Cooper, Christopher B.; Dolezal, Brett A.; Gitlin, Michael; Rawson, Richard A.
Abstract : Background and Objectives: This paper expands on a study investigating depression outcomes in response to an 8‐week exercise intervention among methamphetamine (MA) dependent individuals in early recovery. Methods: A total of 135 MA‐dependent individuals enrolled in residential treatment were randomly assigned to either a structured exercise intervention or a structured health education control group. Both groups were similar in format: 60‐minute sessions, offered three times a week over an 8‐week study period. Results: Results showed that at the 8‐week trial endpoint, participants randomized to the exercise intervention showed significantly greater reduction in depression symptom scores than participants randomized to the health education group, and that participants who attended the greatest number of exercise sessions derived the greatest benefit. This paper further analyzes study data to uncover individual predictors of depression response to exercise and finds that among participants randomized to exercise treatment, individuals with the most severe medical, psychiatric, and addiction disease burden at baseline showed the most significant improvement in depressive symptoms by study endpoint. Conclusions: Our findings suggest that exercise in moderate dose is effective at treating depressive symptoms in individuals in early recovery from addiction, and furthermore, that treatment with exercise appears to be particularly beneficial to individuals who suffer from severe medical, psychiatric, and addictive disorders. (Am J Addict 2015;24:246–251)